Phantom busters. 2 - Shoco (Shonen Jump manga., 2023)
Straight A student Eugene Korekishi doesn't believe in ghost.. but his classmate Mogari Shishikuno is an exorcist who swallows them whole! Mogari can't see ghosts on his own, but once he and Eugene meet someone with the sight, there's only one path left---form an exorcist club at school and embark on anything but a normal high school life! In their search for a fourth member for the club, Mogari Eugene, and new recruit Kaoru Kanzaki set their sights on Kotaro Tamon, a classmate who seems to be able to talk to ghosts, Unfortunately, Kotaro's got some major problems communicating with living humans! Will Kotaro be able to overcome his anxiety and join the Phantom Busters?